POSISI STRATEGI BERSAING BISNIS PEMBENIHAN UDANG VANAME DENGAN PENDEKATAN COMPETITIVE PROFIL MATRIX - Marcus Remiasa; Terry Sugiharto (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2019)
The business competition of vannamei shrimp seed has strongly expanded by the increasing of Indonesian shrimp export. The businessman competesin preparing vannamei shrimp seed for Indonesian fisherman. The ability of competition has influenced in company competitive strategy. Thisresearch aimed to identify the position of competitive strategy and to know the strong and low point of critical success factor (CSF) in the businessof vannamei shrimp seed. This research used descriptive qulaititative research by using phenomenology. The technic of data collecting usedinterview and direct observation to the research subject. The research result by using Competitive Profile Matrix (CPM) showed that the positionof competitive strategy in PT Semar Emas is not strong enough yet as its competitor, PT Dewa Ndaru. The competition ability of PT Semar Emascan be showed in critical success factor (CSF) with the low point in the old company management, the traditional marketing management, thegovernment policy and unstable economic condition. The strong point is in the product location of vannamei shrimp seed and the quality of humanresource.